Kritik Al-Ghazali serta Pembelaan Ibnu Rusyd dalam Menyikapi Rasionalitas dan Wahyu - Riswan R; Indo Santalia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The Islamic Golden Age (approximately the 8th to the 13th century CE) was a pivotal period in world civilization, marked by rapid advancements in various fields such as knowledge, philosophy, medicine, astronomy, and theology. During this era, cities like Baghdad, Cairo, and al-Andalus emerged as vibrant centers of scientific and intellectual activity. A key aspect of this period was the translation of Greek philosophical and scientific works—particularly those of Aristotle—which sparked debates between rationalist thinkers and traditional theologians. Two major figures of Islamic thought from this era, Abu Hamid al-Ghazali (1058–1111) and Abu al-Walid Ibn Rushd (1126–1198), played central roles in shaping the intellectual landscape of Islam. Al-Ghazali emphasized the primacy of revelation as the ultimate source of truth, whereas Ibn Rushd defended the view that philosophy and religion are not inherently contradictory. This article examines the contributions of these two scholars and explores the intellectual tensions that arose between rationality and revelation within the broader discourse of Islamic thought.